Pemanfaatan Media Sosial dalam Perluasan Jangkauan Pasar bagi Produk Usaha Kecil Desa Kuripan Timur - abd.rahman syarif syarif; Sabila Rahmadani; Karomatul Ulya; Ni Ketut Trisnati Ardiantari; Shaufi Kartika Ningrum; Intan Novia Rosiana; Muliana Islami; Yuni Maulida Afifah S.R; Moch. Hisyam Almusalli; Reiki Dwi Wahyu; I Ketut Budastra (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Kuripan Timur Village, Kuripan District, Lombok Barat Regency is a village where most of the people work in agriculture and as an entrepreneur. The community as business actors has not been able to reach consumers widely due to a lack of knowledge about digitalbased media/media that is able to promote the products of local entrepreneurs. To develop Small and Medium Enterprise (UMKM) owned by residents of Kuripan Timur community, it is necessary to take action in promoting their products using social media, especially related to digital marketing. In this activity, people there are not only introduced but also trained in using social media which will make it easier to market products. In addition, people are equipped with procedures for editing pamphlets to be promoted on social media with an easy-to-use app. The assistance is carried out to ensure the community'sunderstanding on how to use social media and the application used to make pamphlets. Keywords: Eastern Kuripan’s People, Digital Matketing, Mikro Small and Medium Engerprises